HISTORICAL AND LEGAL ASPECTS OF FORMATION OF CIVIL SOCIETY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines the historical development of civil society and is of greatest value. The problem of its formation and development is very important, especially in connection with the practical need to create a modern universal civil society.